Experiences of health professionals treating women diagnosed with cancer during pregnancy and proposals for service improvement. (June 2022) - Stafford, Lesley; Sinclair, Michelle; Gerber, Katrin; Christobel Saunders,; Ives, Angela; Peate, Michelle; Lippey, Jocelyn; Umstad, Mark P.; Little, Ruth
Abstract: Objective: To examine the experiences, needs, and perceptions of health professionals(HPs) treating women diagnosed with cancer during pregnancy(gestational cancer, GC). Methods: Interviews were undertaken with Australian HPs who had treated women diagnosed with GC over the previous five years. HPs were recruited via social media, and professional and community networks. Questions focussed upon HPs' confidence caring for these women, whether current guidelines/training met their needs, psychological impacts of care provision, and service gaps. Interview data were analysed thematically. Results: Twenty-seven HPs were interviewed; most were oncology HPs(22/27) with experience caring for women with gestational breast cancer and 13 had a breast-specific clinical focus (e.g. breast surgeon). Many were currently treating women with GC(48%) or had in the last 6–12 months(29.6%). Four themes were identified: A clinically complex case, Managing multi-disciplinary care, C entralised resources for health professionals, and Liaison, information and shared experiences for women . HPs found this population personally challenging to treat. They reported initial uncertainty regarding treatment due to infrequent exposure to GC, limited resources/information, and the need to collaborate with services with which they did not usually engage. Solutions offered include centralised resources, clinical liaison/care coordinators, and connecting women with GC with peer support. Conclusions: HPs perceived women with GC as a vulnerable, complex population and experienced challenges providing comprehensive care; particularly when treatment was delivered at geographically separated hospitals. Systemic changes are needed to optimise comprehensive care for these women. Their insights can guide the development of more integrated cancer and obstetric care, and better HP support. Highlights: Women with cancer diagnosed in pregnancy require complex, coordinated, multidisciplinary care. Clinicians consider these women vulnerable with needs that are hard to meet using standard care. Systemic changes like co-locating services and integrating supportive care are needed. Access to centralised, coordinated, up-to-date evidence-based guidelines is required. Formalised ways to connect women with cancer in pregnancy with peer support would help.